Mengukur Suhu Ruang dan Objek Dengan Menggunakan Suhu Inframerah MLX90614 Berbasis Arduino - Liszulfah Roza; Haflan Nur Iman; Fakhira Nursabrina; Adila Nailufar; Ghina El Hidayah; Ahmad Sofyan Sulaeman (TIME in Physics, 2023)
Temperature measurement is needed in today's laboratory environment. Various sensors have been developed to meet these needs. One of them is an infrared temperature sensor that is used to measure temperature without the need to come into contact with the object whose temperature is to be measured, commonly called contactless. In the project we created, we used the MLX90614 infrared temperature sensor based on Arduino Uno to measure 2 objects alternately, the first is the ambient or room temperature and the second is body temperature. The measurement is carried out without touching and is 1–2 cm from the object being measured. The LCD will display the measurement output in real-time every second using ℃ units. The results of room temperature measurements that have been carried out with the MLX90614 infrared temperature sensor are compared with the results of digital hygrometer room temperature measurements while the results of body temperature measurements carried out with the MLX90614 infrared temperature sensor are compared with the results of thermo gun measurements.